Effect of Atomic Number on Plasma Pinch Properties and Radiative Emissions - Sahyouni, Walid; Nassif, Alaa (Advances in High Energy Physics, 2021)
The aim of the research is to examine the dependence of plasma pinch properties and radiation emissions on the atomic number of the operating gas within the dense plasma focus device (NX2) when using hydrogen and argon gases. Simulation was performed with Lee’s code on an NX2 dense plasma focus at a constant gas pressure value (P0=0.5 torr). The results showed that the minimum radius of the plasma focus in the case of the hydrogen plasma pinch was 0.30 cm and in the case of the argon plasma pinch 0.17 cm, and this affected the value of the radiation emission as it was 7.8×10−6 J and 11 J for the hydrogen and argon pinch, respectively. The energy of the ion beam released by the breakdown of the plasma pinch was found as En=23.8 J in the state of hydrogen and En=105 J in the state of argon.